THRUSHES: REASONS FOR THEIR USE IN STUDIES OF ANIMAL ECOLOGY - Vogel, Huilquer Francisco (SaBios-Revista de Saúde e Biologia, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> <div style="border-right: medium none; -moz-border-top-colors: none; -moz-border-right-colors: none; -moz-border-bottom-colors: none; -moz-border-left-colors: none; -moz-border-image: none; padding: 1pt 0cm 0cm; border: 2.25pt medium medium solid none none #003366 -moz-use-text-color -moz-use-text-color;"> Considering the trials necessary to establish new ecological models and hypotheses, this review aims to propose the use of birds from the genus Turdus as an animal model in studies of animal ecology. Research with this group could be conducted in various locations worldwide, resulting in new methods of animal ecology, with systematic information obtained by several research groups throughout the area that species of this group occur. Among some attributes that ecological studies of these birds provide are: i) these birds abound in urban and forest environments, ii) some species of this group are sensitive to habitat disturbance; iii) some species have plasticity and resistance to environmental disturbances; iv) reasonable catchability; v) most birds of this group have territorial habits; vi) most species have migratory and partially migratory habits; and vii) the species have diverse feeding habits. In that sense, ecological studies about this group could even support conservation strategies for species under certain degrees of endangerment. SABIÁS: MOTIVOS PARA UTILIZÁ-LOS EM ENSAIOS DE ECOLOGIA ANIMAL RESUMO Frente à experimentação necessária para o estabelecimento de novos modelos e hipóteses ecológicas, este comentário teve por objetivo propor a utilização de aves do gênero Turdus, como animal modelo em estudos de ecologia animal. Pesquisas com este grupo podem ser conduzidas em diversos locais do planeta, obtendo novos métodos sobre ecologia animal, com informações sistematizadas obtidas por diversos grupos de pesquisadores ao longo da área de ocorrência de espécies do grupo. Entre alguns atributos que propiciam estudos ecológicos destas aves, pode-se destacar o fato de serem: i) aves abundantes em centros urbanos e ambientes florestais; ii) algumas espécies do grupo são sensíveis à perturbação de habitat; iii) outras possuem plasticidade e resistência a distúrbios ambientais; iv) razoável capturabilidade; v) grande parte das aves do grupo possuem hábitos territorialistas; vi) espécies com hábitos migratórios e parcialmente migratórios e vii) espécies com hábitos alimentares diversificados. Neste sentido, estudo ecológico do grupo, pode subsidiar até mesmo estratégias conservacionistas para espécies que estão sob algum grau de ameaça. <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> <div style="border-right: medium none; -moz-border-top-colors: none; -moz-border-right-colors: none; -moz-border-bottom-colors: none; -moz-border-left-colors: none; -moz-border-image: none; padding: 1pt 0cm 0cm; border: 2.25pt medium medium solid none none #003366 -moz-use-text-color -moz-use-text-color;">